Avaliação imunológica na doença do enxerto contra o hospedeiro crônica - Renata Goncalves de Resende (2013)
The graft-versus-host disease (GVHD) is a major cause of morbidity and mortality after allogeneic hematopoietic stem cell (allo-HSCT). It is known that knowledge about the pathogenesis of chronic GVHD (cGVHD) remains fragmented and few studies show the contribution of inflammatory cytokines in the levels of these mediators and their impact on cGVHD. This study aimed to evaluate the genotypic and phenotypic expression of genes involved in immunoinflammatory response in cGVHD. The study was conducted in two parts: the first part, we obtained samples of saliva and blood of patients and their donors for analysis of polymorphisms in genes IL1B, IL6, IL10, IFNG, TNFA, IL17A and IL17F for measurement of these cytokines by means of PCR and by ELISA, respectively. For the second part of the study, were also collected blood samples from eight other patients with oral cGVHD, four patients undergoing allo-HSCT who did not develop cGVHD and 3 healthy individuals, not transplanted. These samples were subjected to cytogenetic analysis by flow cytometry to determine the levels of cytokines (IL-6, IL-10, IL-17A, IFN- and TNF-) and markers of activation repertoire and cell (CD4, CD8, CTLA-4, Foxp3 and CD25). The results of the first part of the study, forty-two of the 58 patients could be evaluated for systemic cGVHD and 27 for oral cGVHD. It was noted that patients with oral cGVHD histology showed increased levels of IFN-, saliva, and IL-1 in the blood and saliva. For oral clinical GVHD, we observed higher blood levels of IL-6 and lower blood levels of IFN-, plus low levels of IL-1 in saliva. Association was found between the occurrence of systemic cGVHD and IL17A gene polymorphisms in patients. ILIB polymorphism was related to oral cGVHD and IFNG polymorphism was associated with the absence of oral disease. The phenotype high producer TNFA gene donor was related to the presence of oral cGVHD. Already immunophenotyping experiments showed an increased expression of TNF- in CD4 T cells in patients with oral cGVHD compared with transplant patients without the disease and healthy individuals. The expression of CTLA-4, IL-10, IL-17A and TNF- in CD4 cells and IFN- in CD4 and CD8 cells in different conditions of stimulation, were related to oral cGVHD. Finally, HSCT patients showed higher expression of TNF- in relation to individuals not HSCT. Thus, the findings show a genotypic and phenotypic profile proinflammatory related to GVHD, both oral and systemic.